ALTERAÇÃO DAS FUNÇÕES ORAIS E SEU IMPACTO NA QUALIDADE DE VIDA DE ADOLESCENTES - MALUF, Valéria Maria Costa Teixeira (2020)
This study aimed to analyze the impact of changes in oral functions (chewing, swallowing, breathing and phonation) on the quality of life (QOL) of adolescents enrolled in public and private schools in a capital city in northeastern Brazil. This is a population-based cross- sectional study with adolescents of both sexes and the age of 12 years. The data collection period was from March to September 2012, the sample consisting of 332 adolescents. Prior to data collection, a pilot study was carried out considering all the variables involved. The evaluations were made by two collection teams, each team with an interviewer and an examiner (orthodontist). The team was properly trained to apply the questionnaire and perform a clinical dental examination. The diagnostic reproducibility (intra and inter- examiner) was estimated by the Kappa test and by the intraclass correlation test, accepting minimum values of 0.7 Clinical data were collected at school under a natural light source, with the functional changes of the stomatognathic system (SE): breathing, phonation, chewing and swallowing being the main independent variables. The collection of non-clinical data was done through a questionnaire composed of demographic data. To assess the impact of changes in oral functions on QOL, the Oral Health Impact Profile -14 (OHIP-14) was used, with QOL as the dependent variable. The data were analyzed using the resources of the software STATA version 16.0 (StataCorp., CollegeStation, TX, USA) and the descriptive statistics included measures of frequency, median and interquartile range. Nonparametric tests for continuous variables Mann-Whitney and Kruskal-Wallis were used when appropriate. Logistic regression analysis was used to determine the adjusted odds ratio (OR) measure and respective 95% confidence interval (95% CI) for the association between functional changes in SE and QoL related to oral health. The analysis of the association between oral function and OHIP-14 severity showed a higher level of severity among those who had changes in breathing time with sealed lips (P = 0.004), changes in the mirror test (P = 0.005) and masticatory pattern unilateral (P = 0.001). Changes in oral functions negatively impacted the QoL of the children assessed. Each function of the stomatognathic system influenced the dimensions of the OHIP- 14 instrument differently.